How do ability peer effects operate? Evidence on one transmission channel. Issue 3 (4th May 2018) - Kiss, David
ABSTRACT: Many (quasi-)experimental studies show that students tend to learn more in classes with better peers. However, the (presumably numerous) factors mediating the positive relationship between peer and own achievement have received less attention in the literature. I present evidence on one particular transmission channel: teachers tend to grade tougher in classes with better students, inducing parents to send their children to remedial tutorial lessons which have a positive effect on student outcomes. This study provides an example for negative peer ability externalities that are (over-)compensated by parental educational investments.